Entangled complexity: Why complex interventions are just not complicated enough. (January 2013) - Cohn, Simon; Clinch, Megan; Bunn, Chris; Stronge, Paul
The shift of health care burden from acute to chronic conditions is strongly linked to lifestyle and behaviour. As a consequence, health services are attempting to develop strategies and interventions that can attend to the complex interactions of social and biological factors that shape both. In this paper we trace one of the most influential incarnations of this 'turn to the complex': the Medical Research Council (MRC) guidance on developing and evaluating complex interventions. Through an analysis of the key publications, and drawing on social scientific approaches to what might constitute complexity in this context, we suggest that such initiatives need to adjust their conceptualisation of 'the complex'. We argue that complexity needs to be understood as a dynamic, ecological system rather than a stable, albeit complicated, arrangement of individual elements. Crucially, in contrast to the experimental logic embedded in the MRC guidance, we question whether the Randomised Controlled Trial (RCT) is the most appropriate method through which to engage with complexity and establish reliable evidence of the effectiveness of complex interventions.